Systematic literature review: strategic leadership practices among school leaders in Malaysia - Jaafar, Mariani; Asimiran, Soaib; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2022)
Changes in the world of education have provided an avenue for the introduction and application of various discoveries of leadership concepts, to ensure that the quality of education is in line and meets the demands of current changes. Futuristic and contemporary terminology and philosophy of strategic leadership should be practiced by school leaders to manage educational changes. Looking at the educational changes and to achieve the aspiration of Malaysian Education Blueprint (MEBP) 2013-2025, it is relevant and appropriate for school leaders to practice strategic leadership in school. Therefore, the study was conducted to identify the level and impact of strategic leadership practices on the quality and academic exellence of the schools in the last six years. This systematic literature review (SLR) allows reseacher to conduct an explicitly examination of strategic leadership practices among school leaders in Malaysia. A total of 1214 articles were analysed by synthesising it through the four levels of Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA). Resources were searched through four main databases namely SCOPUS, ERIC, Science Direct and Google Scholar. 10 articles that met the criteria and conditions of the study were reviewed. The analysis found that, elements of anxiety or dissatisfaction with the status quo, strategic orientation and strategic translation are given priority. In order to achieve high-quality education and sustain school academic excellence, school leaders need to coordinate all nine elements at an optimal level. Overall, the analysis shown that the strategic leadership practices of school leaders in Malaysia are at a high level and it provides positive and significant impacts on the academic performance and quality of education. The implications of the study can be leveraged for further studies. Future studies proposed to be conducted in qualitative studies or mixed methods in support of strategic leadership practiced by school leaders.